Pemberdayaan Perempuan Baduy Luar dengan Calistung dan Edukasi Kesehatan Untuk Mencapai Sejahtera - Siregar, Tatiana; Ritanti, Ritanti; Permatasari, Indah; Utari, Dyah (Penerbit Goodwood, 2025)
Purpose: The Abdimas team aims to empower Baduy women to read, write, and count, as well as provide health education related to PHBS and demonstrate a healthy toilet renovation Methodology/approach: The community service activities were carried out in Kanekes Village, Baduy Luar, from May to July 2024. The community service approach involved training 40 Baduy women to participate in health education and simple reading, writing, and counting training over three months, including building an example of a healthy toilet Results/findings: Of the 40 who participated until the final evaluation, only 15 remained. This is related to the constraints of the distance to the location, which is far from their homes (activities are centered at the Jaro official residence), and the establishment of a healthy place to wash, bathe, and use the restroom (MCK). Conclutions: The enthusiasm of Baduy women to improve family welfare and increase knowledge is very strong, but it requires support from the local government to assist residents by conducting reading, writing, and arithmetic classes in small groups in adjacent houses. Additionally, there is a need for financial support for the renovation of healthy public toilets. Limitations: The duration of the program may not be sufficient to measure the long-term impact on family well-being and changes in health behavior. Contribution: This community services provides a contextual approach to empowering women in indigenous communities such as Baduy Luar, which are typically seldom reached by modern education and health interventions